If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3 + 4x) = 21 (3 * 3 + 4x * 3) = 21 (9 + 12x) = 21 Solving 9 + 12x = 21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-9' to each side of the equation. 9 + -9 + 12x = 21 + -9 Combine like terms: 9 + -9 = 0 0 + 12x = 21 + -9 12x = 21 + -9 Combine like terms: 21 + -9 = 12 12x = 12 Divide each side by '12'. x = 1 Simplifying x = 1
| 42-8x=14+6x | | 108=-2(2+8v) | | 11x+9x=140 | | -9+-8(-9q+-8)= | | 7t-2t=20-4+9 | | -3x-6+9x=-4x+6 | | 4k+1+3k=-6 | | 6(2x+10)=72 | | 1.75+0.35=2.80 | | 3(1-2x)=-5(3x-2) | | 8x-4=19-3x | | 2(w+5)+2w=70 | | V=imh | | -3(x-6)=-3-3x | | 2(4v-6)-2v=-8+5v | | 4y-3y-1=8 | | 2x-8=2(x-5) | | 2(3x+5)+2(8)=112 | | 0.25p=30 | | -5=-7(x+3)-3x | | 91-(6x+15)=6(x+4)+x | | 7x+17-5x+17=6 | | 21-8=x | | 5x-30=5x+30 | | 2m-m=13+16 | | 0.3(-0.9+8x)=3.2x | | 0.15-0.03(x+2)=-0.01(3-x) | | 1.33n+2n=-6.33+1.75n | | 8x+4x+7y=180 | | 2.4=14.4 | | 12x+(4x-1)=36 | | 1x+8=3 |